How employers rule our lives: An interview with Elizabeth Anderson. Issue 2 (13th September 2017) - Lawrence, Mathew
Abstract : Why our workplaces are private governments, why we can't see it, and what should be done. IPPR Progressive Review's Mathew Lawrence interviews the leading moral and political philosopher Elizabeth Anderson on good work, relational equality, and a fair constitution of the firm.